КОГНИТИВНЫЕ АСПЕКТЫ СЕМАНТИЧЕСКОЙ ДЕРИВАЦИИ ПРОИЗВОДНЫХ СЛОВ (Eurasian Journal of Philology Science and Education, 2015)
The paper aims to clarify the semantic, cognitive featuresof derivative words in English. The article analyses first thedifferent points of views of distinguished linguists andsummarizes their thoughts. The main characteristic feature ofderivative words is its motivated character, the conditionality ofits meaning with its initial unit. All the characteristic features ofderivative words allow a person to form derivative lexical unitsin accordance with its pragmatic intention.